Performance Relay Assisted Wireless Communication Using VBLAST - M.M. Kamruzzaman (Institute of Advanced Engineering and Science, 2014)
In this paper, performance of relay assisted wireless link is evaluated using VBLAST in the presence of rayleigh fading where source is equipped with two transmit antennas, relay is equipped with multiple transmit and multiple receive antennas, and destination has multiple receive antennas. The input information are modulated using QPSK or 16 QAM or 64 QAM modulator and modulated information are encoded using VBLAST and then split into streams which are simultaneously transmitted through transmit antennas of source.Relay decodes the rayleigh fading effected signal and re-encodes using VBLAST and forwards for destination. It is observed that relay with 2 transmit antennas and 2/3/4/5/6 receive antennas provides 9-11.5 dB gains compared to direct link. And there are around 3 dB to 11 dB gains for increasing number of receiving antennas at relay and destination from 2 to 3/4/5/ 6. DOI: http://dx.doi.org/10.11591/telkomnika.v12i8.6031